Use of Carbon Fibers to Enhance the Physical and Mechanical Properties of Wood Composites - Thivagar, Sugumaran (2013)
Medium Density Fiberboard is one type of board used widely in wood industry. Malaysia is one of the top exporters of MDF in the world. These boards becoming less popular in market due to low physical and mechanical strength. This research is on increasing the mechanical and physical property of MDF board by using carbon fiber as filler. The carbon fiber has the ability to increase mechanical properties of MDF. The main purpose of this research is to enhance the mechanical properties of the wood composite boards and the surface smoothness of the boards. The carbon fiber is first treated with nitric acid to modify the surface. The treated carbon fiber then used in the manufacturing of MDF boards. The different percentage of carbon fiber was used for comparing the results. The result shows that, adding carbon fiber as filler had improved the MOR, IB and thickness swelling values, as compared to standard board. So, it proved that the carbon fiber can improve the thermal and mechanical properties of wood composites. As a conclusion, the improvement of mechanical properties of wood composites will increase the demand of Malaysian MDF in global market.